Arsenic exposure assessment of children living in a lead mining area in Southeastern Brazil Avaliação da exposição de crianças ao arsênio em área de mineração de chumbo na Região Sudeste do Brasil - Alice Momoyo Sakuma; Eduardo Mello De Capitani; Bernardino Ribeiro Figueiredo; Franca Durante de Maio; Monica Maria Bastos Paoliello; Fernanda Gonçalves da Cunha; Maria Cristina Duran (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
Environmental contamination by arsenic compounds in the Ribeira River Valley, São Paulo, Brazil has already been observed. Lead mining and refining activities had been carried on since late colonial times and finished recently, at the end of 1995. The source of As in the region is known to be mainly from arsenopirite geological presence in the lead ore. Chronic exposure to arsenic compounds may cause peripheral vascular disorders, hyperpigmentation, hiperkeratosis and cancer of the skin, bladder, lung, liver and other internal organs. The purpose of this study was to assess children exposure to arsenic from environmental sources in the region. Urine samples from children between 7 to 14 years old were collected at the following localities: Cerro Azul (Paraná); urban areas of Ribeira (São Paulo) and Adrianópolis (Paraná); Vila Mota neighborhood (rural area of Adrianópolis) and Serra neighborhood (Iporanga, São Paulo), identified as groups 1, 2, 3 and 4, respectively. Group 1 was considered as non-exposed control group. Toxicologically relevant forms of As were determined by atomic absorption spectrometry with hydride generation system. The median values of urine arsenic levels obtained in groups 1, 2, 3 and 4 were respectively: 3.60, 6.30, 6.41 e 8.94μg/L. Contaminação ambiental por compostos de arsênio no Vale do Ribeira, São Paulo, Brasil, tem sido já observada. As atividades de mineração e refinamento do chumbo têm ocorrido desde a época colonial e foram encerradas recentemente, no final de 1995. A principal fonte de arsênio na região é arsenopirita que ocorre geologicamente no minério de chumbo. Exposição crônica aos compostos de arsênio podem causar desordens vasculares periféricas, hiperpigmentação, hiperqueratose, além de câncer de pele, bexiga, pulmão, fígado e outros órgãos. O objetivo do presente estudo foi avaliar a exposição de crianças ao arsênio proveniente de fontes ambientais na região. Amostras de urina de crianças entre 7 e 14 anos foram coletadas das seguintes localidades: Município de Cerro Azul (Paraná); região urbana dos municípios de Ribeira (São Paulo) e Adrianópolis (Paraná); bairro Vila Mota (área rural de Adrianópolis) e bairro Serra (Ipiranga, São Paulo), identificados como grupos 1, 2, 3 e 4, respectivamente. O grupo 1 foi considerado não exposto (grupo controle). As formas de arsênio toxicologicamente relevantes foram determinadas por espectrometria de absorção atômica com sistema de geração de hidretos. Os valores medianos de arsênio obtidos nos grupos 1, 2, 3 e 4 foram iguais a 3,60, 6,30, 6,41 e 8,9μg/L.